Strategi Adaptasi Komunikasi Multikultural Mahasiswa Luar Jawa: Perspektif Komunikasi Islam - Kholil, Mukhammad Nur (UIN Sunan Ampel Surabaya, 2025)
This study examines the multicultural communication adaptation strategies of non-Javanese students at UIN Sunan Ampel Surabaya, focusing on how they linguistically, socially, and culturally adjust within an academic environment characterized by Islamic values and Javanese culture. The research employs a descriptive qualitative approach, collecting data through in-depth interviews, observations, and document studies, analyzed using Howard Giles’ Communication Accommodation Theory (CAT), which includes the strategies of convergence, divergence, and maintenance. The findings reveal that the adaptation process occurs in three phases: the initial observation and maintenance of one’s original communication style, the adjustment phase through the use of language and behavior aligned with local norms, and the differentiation phase to preserve cultural identity. Digital media such as WhatsApp and Instagram play a significant role in facilitating social adaptation and intercultural communication within the university environment. From the perspective of Islamic communication, these adaptation strategies not only reflect social adjustment but also embody the principles of akhlaqul karimah and Qur’anic communication ethics, including qaulan layyinan (gentle speech), qaulan ma’rufan (kind words), and qaulan kariman (respectful communication). Thus, the adaptation process represents a form of dakwah bil hal, preaching through behavior, that promotes empathy, tolerance, and harmony among cultures. This study highlights that communication adaptation in a multicultural Islamic campus is not merely linguistic accommodation but a manifestation of religious communication ethics fostering inclusive and harmonious academic interactions.